Written/unwritten : diversity and the hidden truths of tenure - Matthew, Patricia A. (University of North Carolina Press, 2016)
"Every scholar of color has a story about reappointment, tenure, or promotion that involves an issue of race. The academy may have a reputation for seeking diversity in its professoriate, but reports from faculty of color around the country make clear that departments and administrators engage in practices that range from unintentional to malignant discrimination. Stories abound of scholars--despite impressive records of publication, superlative teaching evaluations, and exemplary service to their universities--struggling on the tenure track. These stories, however, are rarely shared for public consumption. Written/unwritten reveals that faculty often face two sets of rules when applying for reappointment, tenure, and promotion: those made explicit in handbooks and faculty orientations or determined by union contracts and those that operate beneath the surface"--